2010
DOI: 10.1007/s10534-010-9292-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on 24-hour pattern in expression of redox enzyme and clock genes in rat medial basal hypothalamus

Abstract: The effect of cadmium (Cd) in the brain has been attributed to an increase in reactive oxygen species in cells, particularly when high amounts of the metal are given. In this study we examined the effect of a low dose of Cd (7.5 microg/day) on 24-h changes in expression of redox pathway enzyme and circadian genes in rat medial basal hypothalamus (MBH). Rats receiving CdCl(2) (5 ppm in drinking water) or tap water for 1 month were killed at six different time intervals throughout a 24 h cycle. MBH mRNA levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
4
10
0
Order By: Relevance
“…The data are unpublished results from an experiment reported earlier [[14], see this reference for experimental details]. The sequence of primers used for PCR analysis is described elsewhere [15]. …”
Section: Circadian Disorganization After Hyperadipositymentioning
confidence: 99%
“…The data are unpublished results from an experiment reported earlier [[14], see this reference for experimental details]. The sequence of primers used for PCR analysis is described elsewhere [15]. …”
Section: Circadian Disorganization After Hyperadipositymentioning
confidence: 99%
“…Less information is available on the mediation by redox mechanisms of brain effects of a low concentration of Cd. In a recent study we examined the effect of a low dose of Cd (7.5 μg/day) on 24-h changes in expression of redox pathway enzyme and circadian genes in rat medial basal hypothalamus (MBH; Jiménez-Ortega et al, 2010). In CdCl 2 -treated rats a disruption of 24-h pattern of MBH gene expression of nitric oxide synthase (NOS)-1 and -2, heme oxygenase (HO)-1 and -2, Mn-superoxide dismutase (Mn-SOD), catalase, glutathione peroxidase (GPx), and glutathione reductase (GSR) was detectable.…”
Section: Introductionmentioning
confidence: 99%
“…Mean 24-h levels of MBH mRNA for HO-2, Mn-SOD, and catalase augmented after Cd intake (presumably as a compensatory increase caused by the augmented oxidative load), whereas those of NOS-2 decreased (presumably because Cd causes toxicity independently of NO formation; Wright and Baccarelli, 2007). After CdCl 2 intake, the 24-h pattern of clock gene expression in MBH seen in control rats was significantly disrupted, suggesting that a primary mechanism of action could be on circadian clock mechanisms (Jiménez-Ortega et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Even though, previously, some studies show 24 hours variations in the antioxidant enzymes expression and activity in the mammals' brain, 21,22,39 all of them were done in animals maintained under light:dark (LD) conditions; thereafter, none of them was able to report circadian, endogenously driven, rhythms in the hippocampus. Particularly, previous studies from our and Sewerynek's labs demonstrated that, under LD conditions, levels of CAT and GPx expression and activity vary throughout a 24-hour period in the rat and chicken hippocampus, respectively.…”
Section: Discussionmentioning
confidence: 99%